A study of the effectiveness of inquiry-based learning and project-based learning of science and language subjects at high school level in the U.A.E. - YOUNIS, TAGHREED (2018)
The objective of this study was to investigate the suitability of inquiry-based learning and project-based learning approaches in the science and language at the high school level and their effectiveness. The researcher used a mixed qualitative and quantitative approach in order to accomplish this objective. A two-part survey questionnaire was used to examine the suitability of IBL and PBL to different subjects and the respondents’ perceptions about their use. A comparison of pre and post-test scores of students was used to determine which among the two approaches were more effective. The results show that in terms of suitability, the research instrument focused mainly on IBL. It was found that IBL is most compatible with English, Science, and SPED subjects; and that it is grossly incompatible with Math subjects. It can be inferred based on that that PBL may be the more compatible approach with Math subjects. In terms of effectiveness using the test scores, IBL strategies were more effective. This was evidenced by the bigger impact that using IBL strategies had on the test scores of the respondents compared to when PBL strategies were used. The higher score differentials were observed when IBL was used; the differences between pre and post-test scores were smaller in the PBL group.